Hepatitis B Virus (HBV) Upregulates TRAIL-R3 Expression in Hepatocytes Resulting in Escape From Both Cell Apoptosis and Suppression of HBV Replication by TRAIL. (28th February 2022) - Suehiro, Yosuke; Tsuge, Masataka; Kurihara, Mio; Uchida, Takuro; Fujino, Hatsue; Ono, Atsushi; Yamauchi, Masami; Naswa Makokha, Grace; Nakahara, Takashi; Murakami, Eisuke; Abe-Chayama, Hiromi; Kawaoka, Tomokazu; et al.
Abstract: Background: Hepatitis B virus (HBV) evades host immunity by regulating intracellular signals. To clarify this immune tolerance mechanism, we performed gene expression analysis using HBV-infected humanized mouse livers. Methods: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptor 3 (TRAIL-R3) was significantly upregulated in livers of HBV-infected human hepatocyte transplanted mice by cDNA microarray and next-generation sequencing. We analyzed the significance of TRAIL-R3 upregulation in HBV infection using human hepatocyte transplanted mice and HepG2 cell lines. Results: TRAIL-R3 induction by HBV infection was verified by in vitro and in vivo HBV replication models, and induction was inhibited by antiviral nucleot(s)ide analogue treatment. TRAIL-R3 transcription was regulated by the TRAIL-R3 promoter at −969 to −479 nucleotides upstream from the transcription start site, and by hepatitis B x (HBx) via activation of nuclear factor-κB (NF-κB) signal. TRAIL not only induced cell apoptosis but also inhibited HBV replication. TRAIL-R3 upregulation could inhibit both TRAIL-dependent apoptosis in HBV-infected hepatocytes and TRAIL-mediated suppression of HBV replication. Conclusions: These results suggest a mechanism by which HBV persists by escaping host immunity through upregulation of TRAIL-R3. Development of novel drugs to inhibit this escape system might lead to complete HBV elimination from human hepatocytes. Abstract : HBV infection caused TRAIL-R3 upregulation in both HBV-transfected HepG2 cell lines and HBV-infected mice livers. TRAIL-R3 upregulation inhibited both TRAIL-dependent apoptosis and suppression of HBV replication by TRAIL. HBV might persist by escaping host immunity through upregulation of TRAIL-R3.